The Pine Branch, Senior Number, May 1925 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1925)
The Pine Branch: Senior Number, May 1925. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1925. Includes: editorials, photographs, poems, short stories, and other writings.
Freword | Prologue | First Episode | Alma Mater | Second Episode | Third Episode | Fourth Episode | Epilogue | Locals | Commencement Program
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education